KINERJA PENELITIAN JURUSAN PENDIDIKAN OLAHRAGA (SUATU INVESTIGASI PENELITIANTAHUN 1994 2004) - Caly Setiawan (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
The purpose of this research was to indentify the research performance at the Department of Physical Education during 10 years (1994 2004). This research focused on the facultyresearch documented at the Office of Research, the Yogyakarta State University and student’sthesis of the department documented at both university and faculty library. This research wasdocumentation research conducted by researching the abstract. The instrument used tocollect the data was abstract coding sheet. Research abstracts were categorized into focusingon teaching research, teacher education, and physical education curriculum. The abstractswere coded in various factors including research type, focus, measured variable, and method.The following are the research steps; (1) abstract selection, (2) abstract coding, and (3) dataanalysis. The results show that the research at the Department of Physical Education wasdominated by positivism research.Key words: performance, research, department of physical education, 1994 2004.